2010
DOI: 10.1029/2009jc005748
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale laboratory observations of wave breaking turbulence over an evolving beach

Abstract: [1] Wave breaking turbulence over an evolving beach was observed in a large-scale laboratory flume, as part of the CROss-Shore Sediment Transport EXperiment (CROSSTEX). The data set included comprehensive measurements of water surface elevation, fluid velocity, and morphology for irregular waves under erosive and accretive wave conditions. For the both conditions, the beach reached a quasi-equilibrium state, defined as when the bar shape was stable. Wave breaking characteristics, such as wave heights, average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 53 publications
(125 reference statements)
10
60
0
Order By: Relevance
“…The instrument array was lowered such that the sampling volume of the bottom most ADV was 1.0 cm above the bed at the start of each run. The distances from the bed ( ζ ) to the ADVs were 1.0 cm (ADV1), 5.0 cm (ADV2), 9.0 cm (ADV3), 20.0 cm (ADV4), 31.0 cm (ADV5), and 50.0 cm (ADV6). The signal-to-noise ratio (SNR) threshold and the three-dimensional phase-space threshold method described by Mori et al [21] were used to identify spikes in the ADV data [20].…”
Section: Velocity and Turbulence Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…The instrument array was lowered such that the sampling volume of the bottom most ADV was 1.0 cm above the bed at the start of each run. The distances from the bed ( ζ ) to the ADVs were 1.0 cm (ADV1), 5.0 cm (ADV2), 9.0 cm (ADV3), 20.0 cm (ADV4), 31.0 cm (ADV5), and 50.0 cm (ADV6). The signal-to-noise ratio (SNR) threshold and the three-dimensional phase-space threshold method described by Mori et al [21] were used to identify spikes in the ADV data [20].…”
Section: Velocity and Turbulence Extractionmentioning
confidence: 99%
“…Each turbulent component was estimated using the ST01 method, following Yoon and Cox [20]. In that study, Yoon and Cox [20] used adjacent ADVs to estimate the turbulent components of u, v, and w and showed that the power spectra closely paralleled Kolmogorov's slope of −5/3.…”
Section: Velocity and Turbulence Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruessink, 2010;Grasso et al, 2012) and laboratory (e.g. Scott et al, 2005;Yoon and Cox, 2010) focused on time averaged turbulence quantities at outer flow elevations. Therefore, it remains unclear how breaking generated turbulence may affect time varying turbulent kinetic energy near the bed, inside the wave bottom boundary layer, and how this in return affects sediment transport.…”
Section: Turbulencementioning
confidence: 99%
“…Ting andKirby, 1994, 1995;Yoon and Cox, 2010) and field (e.g. Ruessink, 2010;Feddersen, 2012) studies have addressed the effects of wave breaking on hydrodynamics.…”
Section: Introductionmentioning
confidence: 99%